Diagnosis of asbestosis by a time expanded wave form analysis, auscultation and high resolution computed tomography: a comparative study. Issue 4 (April 1993) - al Jarad, N; Strickland, B; Bothamley, G; Lock, S; Logan-Sinclair, R; Rudd, R M
Abstract : BACKGROUND–Crackles are a prominent clinical feature of asbestosis and may be an early sign of the condition. Auscultation, however, is subjective and interexaminer disagreement is a problem. Computerised lung sound analysis can visualise, store, and analyse lung sounds and disagreement on the presence of crackles is minimal. High resolution computed tomography (HRCT) is superior to chest radiography in detecting early signs of asbestosis. The aim of this study was to compare clinical auscultation, time expanded wave form analysis (TEW), chest radiography, and HRCT in detecting signs of asbestosis in asbestos workers. METHODS–Fifty three asbestos workers (51 men and two women) were investigated. Chest radiography and HRCT were assessed by two independent readers for detection of interstitial opacities. HRCT was performed in the supine position with additional sections at the bases in the prone position. Auscultation for persistent fine inspiratory crackles was performed by two independent examiners unacquainted with the diagnosis. TEW analysis was obtained from a 33 second recording of lung sounds over the lung bases. TEW and auscultation were performed in a control group of 13 subjects who had a normal chest radiograph. There were 10 current smokers and three previous smokers. In asbestos workers the extent of pulmonary opacities on the chest radiograph was scored according to the International Labour Office (ILO) scale. Patients were divided into two groups: 21 patients in whom the chest radiograph was > 1/0 (group 1) and 32 patients in whom the chest radiograph was scored < or = 1/0 (group 2) on the ILO scale. RESULTS–In patients with an ILO score of < or = 1/0 repetitive mid to late inspiratory crackles were detected by auscultation in seven (22%) patients and by TEW in 14 (44%). HRCT detected definite interstitial opacities in 11 (34%) and gravity dependent subpleural lines in two (6%) patients. All but two patients with evidence of interstitial disease or gravity dependent subpleural lines on HRCT had crackles detected by TEW. In patients with an ILO score of > 1/0 auscultation and TEW revealed mid to late inspiratory crackles in all patients, whereas HRCT revealed gravity dependent subpleural lines in one patient and signs of definite interstitial fibrosis in the rest. In normal subjects crackles different from those detected in asbestosis were detected by TEW in three subjects but only in one subject by auscultation. These were early, fine inspiratory crackles. CONCLUSION–Mid to late inspiratory crackles in asbestos workers are detected by TEW more frequently than by auscultation. Signs of early asbestosis not apparent on the plain radiograph are detected by TEW and HRCT with similar frequency. off